2003
DOI: 10.1023/a:1025068419698
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Analysis of Posttranslational Modifications of the Human Large Cytoplasmic Ribosomal Subunit Proteins by Mass Spectrometry and Edman Sequencing

Abstract: The 60S ribosomal proteins were isolated from ribosomes of human placenta and separated by reversed phase HPLC. The fractions obtained were subjected to trypsin and Glu-C digestion and analyzed by mass fingerprinting (MALDI-TOF), MS/MS (ESI), and Edman sequencing. Forty-six large subunit proteins were found, 22 of which showed masses in accordance with the SwissProt database (June 2002) masses (proteins L6, L7, L9, L13, L15, L17, L18, L21, L22, L24, L26, L27, L30, L32, L34, L35, L36, L37, L37A, L38, L39, L41).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Eukaryotic ribosomal proteins are substrates of arginine methylation (18 -21). Proteomic approaches corroborate these findings and indicate that ribosomal proteins contain a variety of covalent modifications, including phosphorylation, acetylation, ubiquitination, methylation of lysines and arginines, and neddylation (22)(23)(24)(25). Notably, asymmetric dimethylarginine is the predominant methylated amino acid in both the eukaryotic 40 and 60 S ribosomal subunits (26).…”
mentioning
confidence: 72%
“…Eukaryotic ribosomal proteins are substrates of arginine methylation (18 -21). Proteomic approaches corroborate these findings and indicate that ribosomal proteins contain a variety of covalent modifications, including phosphorylation, acetylation, ubiquitination, methylation of lysines and arginines, and neddylation (22)(23)(24)(25). Notably, asymmetric dimethylarginine is the predominant methylated amino acid in both the eukaryotic 40 and 60 S ribosomal subunits (26).…”
mentioning
confidence: 72%
“…and Rpl42ab proteins appear to be modified (41). The only human large subunit ribosomal protein known to be modified by lysine methylation is L29 (41); the yeast Rpl29 ortholog is unmodified (18).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further demonstrated that the monomethylation at Lys-40 and Lys-55 in Rpl42 is dependent on two other SET proteins, the Ybr030w gene product and Set7, respectively (16), although the direct enzymatic activity of these proteins has yet to be demonstrated. Several mass spectrometric studies have also identified methyl modifications on ribosomal proteins in plants and mammals (17)(18)(19). Although ribosomal protein methylation appears to be conserved among different organisms, the physiological roles of these lysine methylations remain to be fully elucidated.…”
mentioning
confidence: 99%